TRANSMISSION MECHANISM OF MONETARY POLICY THROUGH ASSET PRICE IN INDONESIA IN THE PERIOD 2002-2011 - Anggraeni, Puspitasari Wahyu (Journal of Indonesian Applied Economics, 2016)
The objective of this study is to identify the transmission mechanism of monetary policy through the assets price in Indonesia. In practice, Bank of Indonesia and the government implements monetary policies by reducing the Loan to Value ratio and by implementing expansionary policy through Housing Finance Liquidy Facility. The method used in this study is the Vector Autoregression First Difference (DVAR). The specific variables used in this study include long-term mortgage interest rates, housing price index, composite stock price index, hot money, money supply and Gross Dometic Product with the observation period starting in 2002:1-2011:12. Some procedures that will be used to support VAR specification including stationary test, cointegration test, Impulse Response Function, and Variance Decompositiion. Based on the DVAR estimates, the asset prices affect the output through the money supply. These results suggest that asset prices do not directly affect output but through some transmission mechanism. The contraction monetary policy implemented by the monetary authority is therefore effective enough to anticipate economic heating caused by the change in asset price.